Muṇṭaśśēri Simpōsiyaṃ - Muṇṭaśśēri, Jōsaph, 1903-1977; Dās, Ai. Vi, 1932- (Vitaraṇaṃ, Dēśābhimāni Bukkhaus, 1978)
Critical articles on the writings of Joseph Mundassery, 1904-1978, Malayalam writer and political activist; read at a symposium.